2021
DOI: 10.3389/fnut.2021.599567
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Healthy Diet Index, Chronic Diseases, Obesity and Lifestyle Risk Factors Among Adults in Kaunas City, Lithuania

Abstract: A healthy and balanced diet is an important factor contributing to overall health and wellness. The aim of this study was to develop a Healthy Diet Index (HDI) score and assess its association with various chronic diseases and lifestyle risk factors. A cross-sectional survey included 1,111 adults aged 18 years and older. Information on dietary habits was collected using a questionnaire. Additional demographic, socioeconomic and lifestyle risk factors data were also collected. Sixteen food groups were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Maintaining healthy eating behavior is essential to avoid the recurrence and exacerbation of AF. According to Dėdelė et al, 36 of 1111 patients with dysrhythmias, patients with poor dietary habits had a 2.5-fold increased risk of developing dysrhythmias. Moreover, a study by Aaby et al 37 on 3116 patients with cardiovascular diseases demonstrated that the health status of patients with cardiovascular diseases was strongly correlated with an unhealthy diet.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining healthy eating behavior is essential to avoid the recurrence and exacerbation of AF. According to Dėdelė et al, 36 of 1111 patients with dysrhythmias, patients with poor dietary habits had a 2.5-fold increased risk of developing dysrhythmias. Moreover, a study by Aaby et al 37 on 3116 patients with cardiovascular diseases demonstrated that the health status of patients with cardiovascular diseases was strongly correlated with an unhealthy diet.…”
Section: Discussionmentioning
confidence: 99%
“…Transferring qualitative data to quantitative for the assessment of diet quality during lockdowns and restricting the variation in the HDI options could also lead to a potential calculation error. However, it is possible to express nHDI and pHDI values in a scale ranging from 0 to 100 [ 22 , 50 ], instead of tertiles [ 51 ], and to determine adherence to a healthy/unhealthy diet (low: <33; medium: 34–67; and high for sum > 67) according to Jezewska-Zychowicz et al [ 50 ]. Therefore, we suggest that before recalculating the indexes (pro-healthy diet index and non-healthy diet index), the authors adapt to one of the two methods listed.…”
Section: Limitationsmentioning
confidence: 99%
“…3 Robust evidence has shown that simple dietary changes can prevent or improve many chronic diseases. [14][15][16] Furthermore, a recent review study recommended the integration of nutrition competencies, such as skill-based nutrition training, into medical education. 17 Moreover, many medical schools in developed countries (USA, UK, and Australia) integrate the culinary medicine curriculum (CMC) into their clinical nutrition curriculum.…”
Section: Introductionmentioning
confidence: 99%